Conversations with Terrence McNally - Frontain, Raymond-Jean 1951-; Frontain, Raymond-Jean 1951- (Literary conversations series, 2023)
"Arriving in New York at the tail end of what has been termed the "Golden Age" of Broadway and the start of the Off Broadway theater movement, Terrence McNally (1938-2020) first established himself as a dramatist of the absurd and a biting social critic. He quickly recognized, however, that one is more likely to change people's minds by first changing their hearts, and-in outrageous farces like The Ritz and It's Only a Play-began using humor more broadly to challenge social biases. By the mid-1980s, as the emerging AIDS pandemic called into question America's treatment of persons isolated by suffering and sickness, he became the theater's great poet of compassion, dramatizing the urgent need of human connection and the consequences when such connections do not take place. Conversations with Terrence McNally collects nineteen interviews with the celebrated playwright. In these interviews, one hears McNally reflect on theater as the most collaborative of the arts, the economic pressures that drive the theater industry, the unique values of music and dance, and the changes in American theater over McNally's fifty-plus year career. The winner of four competitive Tony Awards as the author of the Best Play (Love! Valour! Compassion! and Master Class) and author of the book for the Best Musical (Kiss of the Spider Woman and Ragtime), McNally holds the distinction of being one of the few writers for the American theater who excelled in straight drama as well as musical comedy. In addition, his canon extends to opera; his collaboration with composer Jake Heggie, Dead Man Walking, has proven the most successful new American opera of the last twenty-five years"--